A new dictionary of economics - Taylor, Philip A. S. (New York : A.M. Kelley, 1966)
This dictionary attempts to fill a gap that clearly exists still in the present proliferation of economic textbooks. There's been the extent and nature of the cross-references. The system adopted is the use of small capital letters followed by (qv) for the reference which will clarify the explanation, and small capital letters without (qv) for the cross-reference which is left to the discretion of the reader.
ne 09/09/2021
Ref.
Keywords: Economics